Effect of fabric properties on solar behavior of curtains - Bayar, Güler; Ruzgar, Duygu Gazioglu; Parın, Fatma Nur; Yıldırım, Kenan (İdris Karagöz, 2026)
In this study, we examined how fabric construction, color, and yarn structural parameters affect the solar, ultraviolet (UV), and light transmittance, reflection and absorption properties, as well as the openness ratio of fabric curtains. Panama, 2/1 twill, 3/1 twill, and plain weave fabrics were produced. Using UV/VIS/NIR instruments, we measured the solar properties of all fabrics, calculating their transmittance (solar, light, and UV), reflection (solar and light), absorption (solar and light), and openness ratio. It was found that all solar properties were varied with fabric construction, yarn structure, and color. Solar, light, and UV transmittance values were the most affected by the weft and warp density, and an inverse ratio was found between them. The second major effect came from yarn dullness, which showed an inverse relationship with the transmittance values. Fabric color had the strongest effect on solar and light reflection, with darker colors producing lower reflection levels, while density and yarn dullness also influenced reflection and showed a direct relationship with reflection levels. The effects of fabric texture and yarn structure on reflection were low. The solar absorption rate was most affected by the color parameter, and it was observed that the absorption value increased as the color changed to be darker. The results also showed that fabric density strongly and inversely affected the openness ratio.
Keywords: Fabric Technologies; Kumaş Teknolojisi [EN] Textile Science; Tekstil Bilimi [EN] Textile Sciences and Engineering (Other); Tekstil Bilimleri ve Mühendisliği (Diğer)